Electioneering and Propaganda in Ireland 1917-1920 - CALLINAN, ELAINE MARIE (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2018)
The propaganda and electioneering battles that were conducted by nationalists and unionists, separatists and socialists during the latter end of the Great War and after the armistice compelled transformation and instigated a political and social revolution in Ireland. Embedded in the propaganda messages and themes of political parties were their ideals for the future governance of Ireland. The division that had developed in nationalism at the outbreak of the Great War heightened during the series of by-elections in 1917 and 1918. Compelling propaganda to alter attitudes and reinforce entrenched beliefs was unleashed on the voting public. All parties sought to persuade, and at times manipulate, public opinion to draw attention to and support for their respective causes and their ideologies of home rule, union, or separatism. The outcome of the local government elections of 1920 illuminates on whether 1918 election victories and losses were anomalies or if policies had made inroads into the public consciousness at the local level. The objectives of this thesis are to establish how parties selected their candidates, funded their campaigns, used the variety of methods of propaganda to reveal the shrewdness and skill (or the ineffectiveness) of campaign strategies, contrast the themes, symbols and values, establish the victors and losers, and investigate whether propaganda played a role. The aftermath of the 1916 Rising revived a more bellicose form of Irish nationalism in the form of the Sinn F?in party, and provided a platform for propaganda content and party representatives. Home rule remained suspended, conscription threatened, and Dillon succeeded Redmond as the party leader. By 1917 a political shift amongst a large percentage of the working class within nationalism was underway as favour moved ever more towards Sinn F?in. The entry of Sinn F?in and Labour into political contests intensified competition. A range of propaganda practices delivered the central Unionist policy and a request for collective balloting brought victory in Ulster and areas of Dublin in 1918 and again in 1920. This comprehensive examination into the propaganda campaigns of constitutional nationalists, separatist nationalists, unionists and labour parties in Ireland demonstrates the prevailing contradictory views and ideologies and contributes to the scholarship on Ireland during the revolutionary period 1912 to 1923.
APPROVED
Keywords: Propaganda, Elections, Irish Party, Unionists, Labour, Sinn Fein.